Analisis kemampuan representasi matematis mahasiswa pada mata kuliah sistem geometri berdasarkan latar belakang prestasi belajar mata kuliah geometri transformasi - Mokhammad Ridwan Yudhanegara; Karunia Eka Lestari (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
The purpose of this research i.e. to analyze the ability of student’s mathematical representation in the course of geometry system based on the background of learning achievement of transformation geometry courses. This research is a quantitative research with the exposed facto method. The ex-post facto method is an empirical method of finding that is done systematically, the researcher does not control the independent variables because the manifestation has happened or those variables inherently cannot be manipulated. In this study, the attachment between the ability of mathematical representation and the background of learning achievement of the course of transformation geometry has occurred naturally, and the researchers with the setting want to trace back what are the factors causing it. The research design used is the basic causal-comparative design. Population in this research is all student of semester VI of the academic year 2016